Platform of the Brazilian CSOs: Open Government Data and Crowdsourcing for the Promotion of Citizenship - Ferreira, Raul; Praia, Vagner; Filho, Heraldo; Bonecini, Fabrício; Vieira, Andre; Lopez, Felix (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2017: Anais do XIII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2017.6021, 2017)
In Brazil and around the world, Civil Society Organizations (CSOs) provide valuable public services for society. Through CSOs, people have organized and defended their rights, communities and interests, and can fully exercise their collective potential, often acting in partnership with governments to carry out public policies and/or develop their own projects, financed by the private financing or being self-sucient. Public transparency and availability of quality data are requirements for analyzing the strength and capacity of these organizations. Understanding the distribution of non-governmental organizations across the world and at the national scale, their areas of updating, projects in progress, and their execution capacity, is critical to promote the financing conditions of CSOs, to make it visible and to make it more e↵ective, transparent, and strong. With these goals in mind, we developed the Civil Society Organizations Platform1, an open, free and public on-line portal that provides a wide variety of information on the profile and performance of the population of CSOs in Brazil. Its core mission is to provide data, knowledge, and information on the role played by the almost 400,000 CSOs in activity in Brazil and their cooperation with the public administration in delivering public policies and services. We show how we developed this platform, the integration with several di↵erent databases, the challenges of working with open government data and how we integrated a lot of recent open source technologies in all spheres of system development. The first empirical results are shown and some new features regarding public data are presented.